Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1186/1471-2393-15-s2-s5
|View full text |Cite
|
Sign up to set email alerts
|

Kangaroo mother care: a multi-country analysis of health system bottlenecks and potential solutions

Abstract: BackgroundPreterm birth is now the leading cause of under-five child deaths worldwide with one million direct deaths plus approximately another million where preterm is a risk factor for neonatal deaths due to other causes. There is strong evidence that kangaroo mother care (KMC) reduces mortality among babies with birth weight <2000 g (mostly preterm). KMC involves continuous skin-to-skin contact, breastfeeding support, and promotion of early hospital discharge with follow-up. The World Health Organization ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
142
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(152 citation statements)
references
References 55 publications
(65 reference statements)
5
142
0
1
Order By: Relevance
“…Existing customs, such as carrying the infant on the back, stigma surrounding the birth of a preterm infant and general poor involvement and support from the community may affect KMC. Beliefs that incubator care is more effective than SSC and ambivalence by medical staff may also influence the duration of SSC .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Existing customs, such as carrying the infant on the back, stigma surrounding the birth of a preterm infant and general poor involvement and support from the community may affect KMC. Beliefs that incubator care is more effective than SSC and ambivalence by medical staff may also influence the duration of SSC .…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged direct SSC between infants and caregivers is the cornerstone of KMC . Most studies of KMC have taken place in dedicated KMC wards , where staff were trained to care for both newborn infants and post‐partum women.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The principles are extensively recognised in hospitals, but their application into specific policies and practices involves challenges. For example, in Africa, this practice is considered conventional newborn quality care, but leadership and governance affected the KMC implementation of healthcare workers . An Indian study found that most maternal–child health nurses do not practice KMC, despite a positive attitude towards the method .…”
Section: Introductionmentioning
confidence: 99%
“…The measure of success of KMC not only depends on KMC implementation but also on the utilisation of the service by the beneficiaries, parents with LBWIs [20, 21]. As such, the success of service utilisation largely depends on the utilisation determinants, absence of challenges and barriers, perceived quality of care, cost of care, supportive factors, cultural factors, health system factors and provider factors [20].…”
Section: Introductionmentioning
confidence: 99%